A feasibility study of the expansion of swine and management for Iowa State University’s AG 450 farm - Rinker, Skyler P. (Kansas State University, 2017)
For more than 70 years, the Iowa State University Ag 450 Farm has been in operation south of the Iowa State University (ISU) campus located in Ames, Iowa. The Ag 450 farm is currently the only student managed farm at a land grant university in the United States. The idea for the Ag 450 Farm was developed by Dr. William Murray in 1938 and in 1943, the Ag 450 class was first offered by Dr. Murray. At the farm, the core principals of agribusiness and farm management have been taught while adapting to an ever-changing agriculture. The Ag 450 Farm is considered the capstone course for the Iowa State University Agricultural Studies major. ISU Ag 450 is currently under the supervision of farm manager Greg Vogel and the Iowa State University Agriculture and Studies Department. Today, the Iowa State University Ag 450 students manage approximately 275 acres of owned ground, 700 acres of cash rented ground, 80 acres of crop share ground, and 800 acres of custom farmed ground depending on the year. Ag 450 represents a commercial farming enterprise of corn and soybean production as well as housing nursery piglets and custom finishing over 1000 head of feeder pigs. In its current condition, the ISU Ag 450 is looking to expand its operations to meet the demands Agricultural Studies majors at Iowa State University. A focus of the expansion is to increase the amount of custom finished feeder pigs by building another finishing facility. That type of expansion requires the need for another full-time farm manager. This research examines the feasibility of expansion of the swine and management to determine the impact this may have on the future viability of the farm.
Keywords: Agribusiness; Ag education; Net present value; Feasibility